Digital Ta’aruf and Islamic Da'wah: The Role of Taaruf ID, Salams, and Hawaya in Promoting Islamic Marriage Ethics - Hero Gefthi Firnando; Cucu Setiawati (Dialogia, 2025)
The research aims to examine the role of Islamic matchmaking applications—Taaruf ID, Salams, and Hawaya—in promoting Islamic marriage ethics and serving as a medium for digital da’wah. The rapid development of digital technology has transformed various aspects of human life, including how Muslims approach marriage. This study explores how these platforms align with the Islamic principles of ta’aruf while integrating modern technological advancements. Using a qualitative approach, the research analyzes user experiences, platform features, and Islamic ethical frameworks to assess the extent to which these applications facilitate halal relationships. Findings indicate that these apps offer an alternative to conventional matchmaking methods while maintaining Islamic values. However, challenges such as commercialization, user authenticity, and religious adherence persist. This study contributes to discussions on digital ta’aruf, the intersection of technology and religion, and the evolving landscape of Muslim courtship in the digital era.   REFERENCES Abdullah, Najwa. “2025/7 ‘The Hijrah Phenomenon: Shifting Urban Muslim Identities in Indonesia’ by Najwa Abdullah,” 2025. https://www.iseas.edu.sg/category/articles-commentaries/page/146/articles-commentaries/iseas-perspective/page/2/. Afandy, Mohammad. “The Concept of Matchmaking Through Online Matchmaking Bureaus in the Modern Era. Study of Sociological Analysis and Darurah Rules.” International Journal of Health, Economics, and Social Sciences (IJHESS) 6, no. 2 (2024): 506–13. Al-Dawood, Adel, Serene Alhajhussein, and Svetlana Yarosh. “Saudi Arabian Parents’ Perception of Online Marital Matchmaking Technologies.” Proceedings of the ACM on Human-Computer Interaction 4, no. CSCW3 (January 5, 2021): 1–32. https://doi.org/10.1145/3432910. Alsabela, Zahra, Syamsu Madyan, and Dwi Ari Kurniawati. “TAARUF MELALUI RUMAH TAARUF MYQURAN PRESPEKTIF HUKUM ISLAM.” Jurnal Hikmatina 6, no. 2 (September 6, 2024): 290–305. Asmara, Musda, and Lilis Sahara. “Problems with Choosing a Mate in Islam for People Who Choose a Mate through Social Media.” NUSANTARA: Journal Of Law Studies 1, no. 1 (2022): 40–49. Bagaskara, Ali Akbar, and Roykhatun Nikmah. “Praktik Ta’aruf Online Melalui Aplikasi Ta’aruf Online Indonesia Perspektif Fikih Munakahat.” PhD Thesis, UIN Raden Mas Said Surakarta, 2023. http://eprints.iain-surakarta.ac.id/4197/1/Ali%20Akbar%20Bagaskara.pdf. Concha-Salgado, Andrés, Angélica Ramírez, Beatriz Pérez, Ricardo Pérez-Luco, and Eduardo García-Cueto. “Moral Disengagement as a Self-Regulatory Cognitive Process of Transgressions: Psychometric Evidence of the Bandura Scale in Chilean Adolescents.” International Journal of Environmental Research and Public Health 19, no. 19 (2022): 12249. Davis, Fred D. “Technology Acceptance Model: TAM.” Al-Suqri, MN, Al-Aufi, AS: Information Seeking Behavior and Technology Adoption 205, no. 219 (1989): 5. Dieng, Fama. “Muslims Seeking Marriage in the Digital Age: Key Islamic Ethical Components of Muslim Online Dating.” Master’s Thesis, Hamad Bin Khalifa University (Qatar), 2021. https://search.proquest.com/openview/4a3b1b28a5bb8237851bf3e190d6fd50/1?pq-origsite=gscholar&cbl=2026366&diss=y. Fahrudin, MRFI, and Mohammad Rindu Fajar Islamy. “Da’i (Muslim Preachers) Idols, Fatwas, and Political Constellations: Empirical Study of Millennial Generation Perspective.” Jurnal Dakwah Risalah 33, no. 2 (2022). https://pdfs.semanticscholar.org/5e85/ade5e81bc3990e948d25ad12e1b5c643cd8f.pdf. Figueroa, Timiney. “When Life Demands, Faith Supplies: Empowering Women to Overcome Life’s Challenges by Forging a Relationship Between Faith and Resilience.” PhD Thesis, Virginia Union University, 2024. https://search.proquest.com/openview/9e040e25e600bd63c7f5bc7a22c5c96c/1?pq-origsite=gscholar&cbl=18750&diss=y. Handayani, Dwi Sri. “Ta’aruf Rules in Digital Room: Study of Matchmaking Process on Biro Jodoh Rumaysho Social Media.” Asy-Syir’ah: Jurnal Ilmu Syari’ah Dan Hukum 56, no. 2 (2022): 223–43. Hasan, Farah. “Keep It Halal! A Smartphone Ethnography of Muslim Dating.” Journal of Religion, Media and Digital Culture 10, no. 1 (2021): 135–54. Katz, Elihu, Jay G. Blumler, and Michael Gurevitch. “Uses and Gratifications Research.” The Public Opinion Quarterly 37, no. 4 (1973): 509–23. Klincewicz, Michal, Lily E. Frank, and Emma Jane. “The Ethics of Matching: Mobile and Web-Based Dating and Hook up Platforms,” 2022. https://philpapers.org/rec/KLITEO-8. Lalvani, Simiran, and Joyojeet Pal. “The Moral Orders of Matchmaking Work: Digitization of Matrimonial Services and the Future of Work.” Proceedings of the ACM on Human-Computer Interaction 6, no. CSCW1 (March 30, 2022): 1–23. https://doi.org/10.1145/3512968. Miller, Alexa L. “What Connects Us: A User Experience Frame Analysis Comparison of Secular and Religious Online Dating Sites.” Master’s Thesis, University of Nevada, Las Vegas, 2022. https://search.proquest.com/openview/497b5b2231c332a48d2878e878b77469/1?pq-origsite=gscholar&cbl=18750&diss=y. Musarrofa, Ita, Husnul Muttaqin, and Ridha Amaliyah. “The Problems of Islamic Family Law in the Digital Era and Its Relevance to Renewal of the Compilation of Islamic Law.” Jurnal Hukum Islam 22, no. 1 (2024): 89–124. Mutia, Tika. “Da’wahtainment: The Creativity of Muslim Creators in Da’wah Communication on Social Media.” Jurnal Dakwah Risalah 32, no. 2 (2022): 147. Nisa, Eva F. “Online Halal Dating, Ta’aruf , and the Shariatisation of Matchmaking among Malaysian and Indonesian Muslims.” CyberOrient 15, no. 1 (June 2021): 231–58. https://doi.org/10.1002/cyo2.13. Nugroho, Ishak Tri. “Agency in the Online Matchmaking Platform: Study of Rumah Taaruf myQuran and Mawaddah Indonesia.” Al-Ahwal: Jurnal Hukum Keluarga Islam 14, no. 2 (2021): 200–213. “(PDF) FINDING A SOULMATE THROUGH HALAL MEANS: Online Ta’aruf among Indonesian Muslim Youth.” In ResearchGate, 2024. https://doi.org/10.1355/9789815104950-008. Rahman, Rahman, Ilyas Ilyas, Zulfahmi Alwi, and Zailani Zailani. “Nikah Muda: The Hijrah Movement of Anti-Dating Communities from Progressive to Conservative in Indonesia (A Critical Study of Hadith).” Millah: Journal of Religious Studies, 2024, 67–102. Rochadiat, Annisa Mp, Stephanie Tom Tong, and Julie M Novak. “Online Dating and Courtship among Muslim American Women: Negotiating Technology, Religious Identity, and Culture.” New Media & Society 20, no. 4 (April 2018): 1618–39. https://doi.org/10.1177/1461444817702396. ———. “Online Dating and Courtship among Muslim American Women: Negotiating Technology, Religious Identity, and Culture.” New Media & Society 20, no. 4 (April 2018): 1618–39. https://doi.org/10.1177/1461444817702396. Rohimi, Rikaya, and Zulyadain Zulyadain. “THE QUR’AN’S SOLUTION TO EFFORTS TO PREVENT SEXUAL VIOLENCE (QS ANALYSIS. AN-N? R [24]: 30-31 IN THE TAFSIR AN-N? R).” El-Umdah 7, no. 1 (2024): 16–33. Saat, Norshahril, and Sharifah Afra Alatas. “Society Ana.” Accessed March 4, 2025. Tariq, Urwa. “The Rise of AI-Driven Platforms.” Entrepreneurship in the Creative Industries: Contemporary Perspectives from the Arabian Gulf and Asia, 2025. Wagner, Claire, Barbara Kawulich, and Mark Garner. “A Mixed Research Synthesis of Literature on Teaching Qualitative Research Methods.” Sage Open 9, no. 3 (July 2019): 2158244019861488. https://doi.org/10.1177/2158244019861488.